Potential Activity of Zinc Oxide Nanoparticles and Ethanolic Olive Leaf Extract Against Oxacillin Resistant Staphylococcus aureusin vitro - Al-Ugaili, Dhafar; A, Fadhil A M; Wohaieb, Saleh A (Al-Nahrain Journal of Science, 2018)
This study was carried out to evaluate the enhanced effect of ZnO nanoparticles and a crude ethanolic extract of olive leaves upon the antibacterial activity of oxacillin against oxacillin resistant Staphylococcus aureus (ORSA) isolate from hospital environment. A positive and induced effect for ZnO nanoparticle was detected upon the antibacterial activity of the antibiotic through the increase in the diameter of the inhibition zone for the antibiotic as it recorded (15mm) for the mixed activity to the antibiotic with nanoparticles compared with that of (10mm) for the zinc oxide nanoparticle a lone and the disappearance of the inhibition zone for the antibiotic alone. The antibacterial efficacy of the crude ethanolic olive leaf extract was evaluated alone or in combination with either oxacillin or zinc oxide nanoparticles against oxacillin resistant Staphylococcus aureus using disc diffusion method. The results revealed that olive leaf extracts (2.25-9 mg/disc) neither exhibited antibacterial activity when used alone, nor potentiated the antibacterial activity of zinc oxide nanoparticles (100µg/disc) when used in combination. However, in the presence of the highest concentration of olive leaf extract (9mg/disc), the antibacterial activity of oxacillin (1µg/disc) (as a diameter of inhibition zone) increased from zero mm to a maximum of 14 mm, suggesting a potentiation of the antimicrobial activity of oxacillin against the already existing oxacillin-resistant strain of Staphylococcus aureus.